Two cases with intra‐aortic balloon pumping use for severe septic cardiomyopathy. Issue 4 (13th July 2017) - Hiromi, Taro; Toida, Chiaki; Muguruma, Takashi; Hashiba, Katsutaka; Doi, Tomoki; Nakamura, Kyota; Morimura, Naoto
Abstract : Cases: Septic cardiomyopathy is defined as a reversible left ventricular systolic dysfunction. Patients with severe septic cardiomyopathy have a high mortality rate, even if they receive conventional therapy. For those patients, previous reports showed intra‐aortic balloon pump (IABP) efficacy. We report two rare cases with IABP introduction leading them to drastic improvement, and survival from severe septic cardiomyopathy. Case 1 is a 78‐year‐old woman diagnosed with renal calculus pyelonephritis, septic shock, and septic cardiomyopathy. Case 2 is a 62‐year‐old man diagnosed with pneumonia, septic shock, and septic cardiomyopathy. Outcome: In both cases, despite conventional therapy for cardiomyopathy, including high‐dose catecholamine therapy, shock was not reversed, and the IABP was inserted. Circulatory status was improved after the introduction of the IABP. Conclusion: Our findings suggest that an IABP can be useful for salvaging patients with septic cardiomyopathy who do not respond to conventional therapy. Abstract : The intra‐aortic balloon pump was a highly effective mechanic device in our two patients with severe septic cardiomyopathy. The clinical course of these two cases indicated that the intra‐aortic balloon pump could be useful for managing septic cardiomyopathy that does not response sufficiently to conventional therapy.